Labour Market Institutions and Structural Reforms: A Source for Business Cycle Synchronisation? - Frauke Schleer; Andreas Sachs (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
We focus on the influence of institutional variables on business cycle synchronisation for 20 OECD countries from 1979 to 2003. More precisely, this paper derives measures for similarity of institutions and structural reforms, and investigates direct and delayed reform effects on synchronisation by applying robustness tests to a panel data framework with bilateral data. Our findings indicate a strong instantaneous relationship between both similarity of institutions as well as common structural reforms and business cycle correlation.
Keywords: F42; E32; 330; Business cycle synchronisation; Institutions; Structural reforms; Robustness test; Konjunkturzusammenhang; Institutionelle Infrastruktur; Arbeitsmarktpolitik; Reform; Arbeitsmarktflexibilisierung; OECD-Staaten